2017
DOI: 10.1590/1982-43272768201713
|View full text |Cite
|
Sign up to set email alerts
|

Factorial Structure Validation of the Movement Assessment Battery for Children in School-Age Children Between 8 and 10 Years Old

Abstract: The adaptation of instruments to other cultural contexts is a complex task that requires careful planning to maintain the content and psychometric properties. One of the most used motor assessment tools in the world is the Movement Assessment Battery for Children 2ed. In this study, we evaluated the factorial organization of the MABC-2 for the age group 8-10 years from the perspective of classical and modern psychometric theory. For this purpose, a group of 350 school children in the city of Manaus (AM, Brazil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Information regarding socioeconomic status (SES) was included in one article which stated they sampled from low SES [ 70 ], while two studies recruited samples from indigenous populations (in Australia and Canada, respectively) [ 44 , 71 ], the latter of which focused on the recruitment of children whose mothers drank alcohol during pregnancy [ 71 ]. Studies evaluating the validity and reliability of FMS assessment tools were conducted in 29 countries, with Australia hosting the most studies (13) [ 50 , 56 , 71 77 ], followed by Brazil (12 studies) [ 53 , 57 , 66 , 70 , 78 85 ] and the USA (nine studies). Eight studies were carried out in Belgium [ 49 , 58 , 63 , 86 89 ] and seven in Canada [ 43 , 54 , 60 , 90 94 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Information regarding socioeconomic status (SES) was included in one article which stated they sampled from low SES [ 70 ], while two studies recruited samples from indigenous populations (in Australia and Canada, respectively) [ 44 , 71 ], the latter of which focused on the recruitment of children whose mothers drank alcohol during pregnancy [ 71 ]. Studies evaluating the validity and reliability of FMS assessment tools were conducted in 29 countries, with Australia hosting the most studies (13) [ 50 , 56 , 71 77 ], followed by Brazil (12 studies) [ 53 , 57 , 66 , 70 , 78 85 ] and the USA (nine studies). Eight studies were carried out in Belgium [ 49 , 58 , 63 , 86 89 ] and seven in Canada [ 43 , 54 , 60 , 90 94 ].…”
Section: Resultsmentioning
confidence: 99%
“…Structural validity was assessed by ten studies, with six finding evidence for a three factor (manual dexterity, aiming & catching and balance) model [ 78 , 122 , 126 , 129 131 ]. One study found a four factor solution, with a general factor for age band 1, four factors with balance split into static and dynamic for age band 2, and a 3 factor correlated model for age band 3 [ 132 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To identify signs of DCD and to assess children's motor performance, we used two assessment instruments. The first instrument was the Movement Assessment Battery for Children -Second Edition (MABC-2) (Henderson et al, 2007) as it is one of the most tests used in research to identify DCD, and professionals from different areas use it for this purpose (Santos et al, 2017). Recently, this test was translated and used in children from the southern region of Brazil in an initial validation study for our population (Valentini et al, 2014).…”
Section: Data Collection Procedures and Instruments Usedmentioning
confidence: 99%